2013
DOI: 10.1038/nchembio.1382
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect coordination chemistry facilitates metal ion release in the Psa permease

Abstract: The relative stability of divalent first-row transition metal ion complexes, as defined by the Irving-Williams series, poses a fundamental chemical challenge for selectivity in bacterial metal ion acquisition. Here we show that although the substrate-binding protein of Streptococcus pneumoniae, PsaA, is finely attuned to bind its physiological substrate manganese, it can also bind a broad range of other divalent transition metal cations. By combining high-resolution structural data, metal-binding assays and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
220
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(246 citation statements)
references
References 58 publications
26
220
0
Order By: Relevance
“…The unwinding of the linking helix, characteristic of all metal-bound structures crystallised thus far, [24] was not observed in our simulations of metal-free PsaA, suggesting that this conformational change is only induced upon metal binding. This study characterizes the intrinsic flexibility of metal-free PsaA in solution, providing additional structural information that cannot be obtained from the available crystal structures.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…The unwinding of the linking helix, characteristic of all metal-bound structures crystallised thus far, [24] was not observed in our simulations of metal-free PsaA, suggesting that this conformational change is only induced upon metal binding. This study characterizes the intrinsic flexibility of metal-free PsaA in solution, providing additional structural information that cannot be obtained from the available crystal structures.…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, it remains to be ascertained how the crystallographic structure of metal-free PsaA compares to its conformational flexibility in solution. Previous MD studies of PsaA have examined the structural changes that are induced by removing the metal ion from the metal-bound protein [24]. The series of 50 ns simulations from that work showed that the observed structural changes were consistent with the proposed spring-hammer mechanism [24].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations